1994
DOI: 10.1002/1520-6807(199404)31:2<113::aid-pits2310310205>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Role and function of school psychologists, 1992–93: A comparative study

Abstract: The roles and functions of 52 school psychologists from Iowa and Tennessee were examined. A multivariate analysis of variance (MANOVA) was used to test differences between reported time spent on prereferral. assessment, intervention, consultation, and curriculum-based assessment. Significant differences were found for the time spent in all areas. A second one-way MANOVA was used to test the differences between the two groups in reported actual time spent and desired time spent. A significant difference was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…This is consistent with previous studies in which preferred roles for psychologists included reduced time spent on assessment and increased time spent on direct interventions and problem-solving consultation (Reschly & Wilson, 1995). More than 75% of the respondents in this study, however, devote less than 40% of their time to assessment related activities, which is much less than the 51% spent in assessment related activities by the majority of the school psychologists in other studies (Levinson, 1990;Roberts & Rust, 1994;Brown, Swigart, Bolen, Hall, & Webster, 1998;DeSimone, 1998). Despite reporting decreased time spent on assessment-related activities when compared to previous studies, there continues to be a significant discrepancy between actual and desired time spent on assessment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with previous studies in which preferred roles for psychologists included reduced time spent on assessment and increased time spent on direct interventions and problem-solving consultation (Reschly & Wilson, 1995). More than 75% of the respondents in this study, however, devote less than 40% of their time to assessment related activities, which is much less than the 51% spent in assessment related activities by the majority of the school psychologists in other studies (Levinson, 1990;Roberts & Rust, 1994;Brown, Swigart, Bolen, Hall, & Webster, 1998;DeSimone, 1998). Despite reporting decreased time spent on assessment-related activities when compared to previous studies, there continues to be a significant discrepancy between actual and desired time spent on assessment.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with working in a single school where school psychologists are more integral members of the school staff and have a more diverse set of duties. School psychologists who reported diversity in their roles in past studies also reported higher job satisfaction (Jerrell, 1984;Roberts & Rust, 1994). School psychologists in the expanded role models of service delivery have diversified their roles to include active participation in instructional support programs and student assistance teams as well as other roles not typically associated with school psychologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School psychologists have consistently reported they would like to spend more time engaged in consultation and less time conducting assessments (Costenbader, Swartz, & Petrix, 1992;Reschly & Wilson, 1995;Roberts & Rust, 1994). School psychologists have consistently reported they would like to spend more time engaged in consultation and less time conducting assessments (Costenbader, Swartz, & Petrix, 1992;Reschly & Wilson, 1995;Roberts & Rust, 1994).…”
Section: Barriersmentioning
confidence: 99%
“…Previous research (Fisher et al, 1986;Meacham & Peckham, 1978;Smith, 1984) has documented that school psychologists spend most of their time on cognitive assessment. Given the influence of conducting CBA and the preference for a modified assessment role, perhaps the reform-minded psychologists in this study more closely resembled those in the Wilson (1991) study and some of the participants in the study by Roberts and Rust (1994), whose participants were engaged in statewide training on CBA, prereferral intervention, and schoolbased consultation.…”
Section: Discussionmentioning
confidence: 97%